POTENSI PERMEN TIRAMISU YANG BERKHASIAT ANTIKOLESTEROL - Waliyuddin, Waliyuddin; Yunita, Elvira; Karomah, Nailatul; Irshan, Yusuf; Amellia, Amellia (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2013)
Tiramisu candy is made of oyster mushroom extract ethanol. Oyster mushroom (Pleurotus ostreatus) contains lovastatin that inhibit cholesterol synthesis in the body. Ethanol extract of oyster mushroom was expected to give an effect in lowering cholesterol. This experiment used 35 male Sprague dawley rats that were divided into 5 groups (n=7). The treatment period was for 14 days, normal group fed by standard woof, hypercholesterolemic group (HK) were fed by high- cholesterol woof (3%) and PTU (0.5 mg/kg BW), the group of lovastatin(lovastatin+HK0.2857mg/kgBW), treatment I group (HK+ oyster mushroom ethanol extract 30 mg/kg BW), and treatment II group (HK+ oyster mushroom ethanol extract 60 mg/kg BW). Blood was taken through the eyes of rats with hematocrit-heparin. Candy is made with a mixture of 5% starch, maltodextrin 10%, 4% magnesium stearate, sucrose 81%, and ethanol extract 2.1 grams of white oyster mushroom.The results showed that the ethanol extract of oyster mushroom (30 mg/kg BW and 60 mg/kg BW ) may decrease 53.89% and 66.43% of cholesterol concentration. AST and ALT results of the analysis showed that the ethanol extract of white oyster mushroom dose of 30mg/ kg and 60 mg/ kg did not cause liver damage. Based on HPLC analysis, a gram of oyster mushroom ethanol extract containing 3.6x10- 6 grams of lovastatin. Tiramisu candy successfully made by weight 100 mg to extract content of 2.1 mg and 7.56x10-6mg of lovastatin. Keywords : AST ALT, candy, cholesterol, lovastatin, Pleurotus ostreatus.